Analisis Maqashid Syari’ah Tentang Praktik Jual Beli Hasil Pertanian Dengan Pemborong - Gaussian, Gini; Mauludin, Firman (STAI Al-Musaddadiyah Garut, 2025)
The wholesale system of buying and selling agricultural products emerged when a farmer didn't want to bother and if someone was already buying, the farmer no longer needed to look for a harvester, on the other hand, wholesalers preferred to buy agricultural products through a wholesale system, because buying in bulk was quite profitable. Which became the formula. The problems in this research are 1). What is meant by buying and selling agricultural products using a wholesale system? 2). What is the practice of buying and selling agricultural products using a wholesale system in Cihuni Village? 3). What is the maqashidu sharia analysis regarding the practice of buying and selling agricultural products to wholesalers in Cihuni Village? The aim of this research is to find out how the wholesale buying and selling system is practiced and what the maqashid shari'ah analysis is like. The method used by the author is field research, and this research also uses descriptive methods and analysis with a qualitative approach. The results of the research can be concluded that buying and selling agricultural products in bulk can be considered to support maqasid sharia in meeting people's needs for food. In Islam, ensuring the availability of sufficient food for society is one of the main goals. Keywords: Maqashid Syari'ah, Buying and Selling, Agriculture